Blade capable of effectively reducing wind resistance - YAN CHENGHAO (2025)
The utility model relates to the technical field of blades, and discloses a blade capable of effectively reducing wind resistance, which comprises a plurality of rotating blades, a fixing plate is in threaded connection with the interior of each rotating blade, a connection stabilizing shell is fixedly connected with the top end of each fixing plate, and an insertion stabilizing shell is slidably connected with the interior of each connection stabilizing shell. A connecting pushing cylinder is fixedly connected to the interior of the inserting stabilizing shell, a pushing piece is fixedly connected to the interior of the connecting pushing cylinder, and auxiliary positioning assemblies are fixedly connected to the left bottom end and the right bottom end of the pushing piece correspondingly and used for auxiliary positioning of the pushing piece; the top end of the insertion stabilizing shell is fixedly connected with an auxiliary blade. According to the utility model, errors and errors in the assembling proc